Mexico - Income Generation and Social Protection for the Poor : Volume 2. Urban Poverty in Mexico - World Bank (Washington, DC, 2012)
Half of the moderately poor, and one third of the extremely poor now live in urban areas in Mexico. While cities offer a number of opportunities and specific challenges for the poor, low quality and high costs restrict real access to basic public services. Yet, the urban-rural distinctions need to be seen as a continuum, where depth and characteristics of poverty vary with settlement size. The objective of this report is to inform the design of urban poverty interventions. It is organized as follows. The first section - comprising three chapters - examines what we know about the urban poor, seeking to understand better the dimensions of urban poverty. Chapter 2 considers the relationship between urban poverty and macroeconomic trends, and examines the poor's coping mechanisms, as well as the principal public programs available to them. Chapter 3 relies on a recent survey conducted by Mexico, to look in more depth at life in Mexico's poor urban barrios (neighborhoods). Section two of the report discusses some of the key challenges facing the urban poor, namely how to integrate labor markets and access "good" jobs (chapter 4), while Chapter 5, looks into how to protect - themselves - against income shocks by accumulating assets or accessing financial services.